Yoğun bakım hastalarında soluble urokinase plasminogen activator receptor (suPAR)'ın önemi - (:unkn) unknown (My University, 2013)
ÖZET İnflamasyon ve koagülasyona eğilim, çeşitli kritik hastalık durumlarında anahtar patojenik faktörlerdir. Soluble urokinase plasminogen activator (suPAR) immünolojik olarak aktif hücrelerden salınan, fibrinoliz ve inflamasyonu yansıtan bir belirteçtir. Artmış suPAR seviyeleri, inflamasyon ve nfeksiyon gibi durumlarda immun sistem aktivasyonunu yansıtır. Sistemik inflamatuar yanıt sendromu, bakteriyemi ve sepsiste artmış suPAR düzeyleri bildirilmiştir ve yüksek düzeyler kritik hastalarda kötü prognozla ilişkilendirilmektedir. Bu hasta grubunda suPAR hastalık şiddeti ile ilişkili skorlara benzer prediktif değere sahiptir. suPARın diagnostik önemi, C-reaktif protein CRP) ve prokalsitonin (PCT) gibi diğer belirteçlerle karşılaştırıldığında tam olarak anımlanamamıştır. Bu derlemede, suPARın kritik hastalarda önemine genel bir bakış

SUMMARY Inflamation and tendency towards to coagulation are key pathogenic factors in various conditions of critical illness. Soluble urokinase plasminogen activator (suPAR), is a biomarker of fibrinolysis and inflammation, expressed in immunologically active cells. High serum suPAR concentrations are suggested to reflect the activation of the immune system in circumstances of inflammation and infection. In critically ill patients, elevated suPAR levels in systemic inflammatory response syndrome (SIRS) and sepsis, in which high levels indicate poor prognosis. suPAR may have predictive value similar to disease severity scores in these patient population. The diagnostic value of suPAR has not been well defined, compared to other biomarkers, such as C-reactive protein (CRP) and procalcitonin (PCT). This review provides an overview of the value of suPAR in the critically ill patients.
The significance of soluble urokinase plasminogen activator receptor (suPAR) in ICU Patients
Keywords: Yoğun Bakım, Tıp